High temperature stress during flowering and grain filling offsets beneficial impact of elevated CO2 on assimilate partitioning and sink-strength in rice - Chaturvedi, Ashish K.; Bahuguna, Rajeev N.; Shah, Divya; Pal, Madan; Jagadish, Krishna S.V. (Springer, 2017)
Elevated [CO2] (e[CO2]) environments have been predicted to improve rice yields under future climate. However, a concomitant rise in temperature could negate e[CO2] impact on plants, presenting a serious challenge for crop improvement. High temperature (HT) stress tolerant NL-44 and high yielding basmati Pusa 1121 rice cultivars, were exposed to e[CO2] (from panicle initiation to maturity) and a combination of e[CO2] + HT (from heading to maturity) using field based open top chambers. Elevated [CO2] significantly increased photosynthesis, seed-set, panicle weight and grain weight across both cultivars, more prominently with Pusa 1121. Conversely, e[CO2] + HT during flowering and early grain filling significantly reduced seed-set and 1000 grain weight, respectively. Averaged across both the cultivars, grain yield was reduced by 18 to 29%. Despite highly positive response with e[CO2], Pusa 1121 exposure to e[CO2] + HT led to significant reduction in seed-set and sink starch metabolism enzymatic activity. Interestingly, NL-44 maintained higher seed-set and resilience with starch metabolism enzymes under e[CO2] + HT exposure. Developing rice cultivars with higher [CO2] responsiveness incorporated with increased tolerance to high temperatures during flowering and grain filling using donors such as NL-44, will minimize the negative impact of heat stress and increase global food productivity, benefiting from [CO2] rich environments.